Socio-Economic Background Impacts Academic Goals, Performance, and Achievements among Private University Undergraduates in Chittagong, Bangladesh - Barua, Turjo; Chakma, Saju; Uddin, Azim (American Journal of Education and Practice, 2023)
Purpose: The study aims to examine the impact of socioeconomic status the academic performance of undergraduates in private universities in Chittagong, Bangladesh. It aims to understand the impact of family financial background on students'' academic goals, results, and activities, as well as the role of family, social, and institutional issues in students'' choices and decisions. The study also aims to test students'' understanding and identification of social challenges. Methodology: A mixed-method study in Chittagong City, Bangladesh, examined students'' attitudes on the socioeconomic background's impact on academic aspirations and performance. The study with mixed method strategy collected data from 206 undergrad students at private universities, focusing on academic performance, engagement, and personal lives. Findings: The study found that socioeconomic factors impact students'' academic performance at private universities, with middle-class students from Bangladesh enrolling to complete their education. However, tuition costs and family influences can lead to part-time employment, starting businesses, or discontinuing studies. Institutions and students'' personal desires can help improve academic performance. While some students use the financial crisis of family as inspiration, they lack the necessary tools to manage difficulties and participate in university activities Family socioeconomic background significantly impacts students'' academic performance and extra-curricular engagement, especially in private universities. Poor students face financial constraints and struggle to navigate academic environments. Institutional environments, personal life, and part-time jobs can hinder motivation. Recommendations: The study suggests addressing psychological issues among socioeconomically weak private university students, involving parents, personal lives and studying public-private university challenges. It also recommends interviewing scholarship recipients and training higher education teachers to provide personal guidance and consultancy for students facing mental stress. Soft Hands from families, teachers, peers, and an appropriate institutional environment can improve performance.